2015
DOI: 10.1111/andr.12012
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogenic Escherichia coli (UPEC) induced antimicrobial gene expression in the male reproductive tract of rat: evaluation of the potential of Defensin 21 to limit infection

Abstract: SUMMARYEscherichia coli (E. coli) is a common pathogen in epididymitis, which represents a prevalent entity in male reproductive tract infections (RTI). Although current treatment regimens using antibiotics are satisfactory, development of antimicrobial resistance by the pathogen represents a challenge in the management of RTI. Hence, identification of antimicrobial peptides as alternatives to antibiotics has gained importance. We demonstrate that in a rat epididymo-orchitis model induced with uropathogenic E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Production of antimicrobial peptides is an integral part of innate immunity and is crucial to prevent infections. We previously reported that Defb and Spag11 genes expressed in epididymis and testis are implicated in the endotoxin or bacterial‐induced host responses and that administration of DEFB21 can reduce uropathogenic E. coli load in a rat model of epididymitis (Biswas, Bhushan, Meinhardt, & Yenugu, ; Biswas & Yenugu, , ). Alteration in the expression of innate immune machinery in different organ systems under diabetic conditions is well reported.…”
Section: Discussionmentioning
confidence: 99%
“…Production of antimicrobial peptides is an integral part of innate immunity and is crucial to prevent infections. We previously reported that Defb and Spag11 genes expressed in epididymis and testis are implicated in the endotoxin or bacterial‐induced host responses and that administration of DEFB21 can reduce uropathogenic E. coli load in a rat model of epididymitis (Biswas, Bhushan, Meinhardt, & Yenugu, ; Biswas & Yenugu, , ). Alteration in the expression of innate immune machinery in different organ systems under diabetic conditions is well reported.…”
Section: Discussionmentioning
confidence: 99%
“… 62 86 87 In the testis, atrophy, swelling, edema, and enlargement of the gonad are observed. 77 83 85 In contrast to men, in the animals models testicular weight was unaltered in the initial stages of the disease, 77 86 while a slight decrease in testicular volume was documented at later time points. 88 These changes reflect an acute response to the infection that appears within 24–48 h after inoculation, 54 86 87 88 and are most prominent up to 7–14 days postinfection, then subside and vanish after 1 month.…”
Section: Animal Models Of Epididymitismentioning
confidence: 92%
“…An alternative tool to induce epididymitis is the administration of bacterial lipopolysaccharide (LPS), a major structural component of the outer membrane of Gram-negative bacteria, instead of live bacteria. 24 82 83 LPS is a well-characterized inducer of inflammation. It binds preferentially to TLR4 and induces a signaling cascade involving the accessory receptor proteins, MD2 and CD14, and several adapter proteins, such as myeloid differentiation factor 88 (MyD88).…”
Section: Animal Models Of Epididymitismentioning
confidence: 99%
See 2 more Smart Citations